PERLINDUNGAN HUKUM HAK KEKAYAAN INTELEKTUAL TERHADAP TINDAKAN PELANGGARAN PEMBAJAKAN BUKU ELEKTRONIK MELALUI MEDIA ONLINE - Etry Mike (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2017)
This time progress of science and technology and the increase of national development activities make the sociaty in various aspects of life also experienced an increase therefore the effort of creation and renewal of a legislation is required to be guaranteed a legal certainty. As well as in the field of science art, and literature are closely related to the problem of Intellectual Property Rights, because increasing of technology activities marked by the emergence of innovative new discoveries but unfortunately in the middle development of science and technology sector is not supported by public awareness and market participants to be honest in understanding the importance of protecting Intellectual Property Rights on a product produced by someone. The rise of piracy toward books that happening at this time indicates the weakness of the enforcement of copyright in Indonesia. Books in electronic format should be able to provide a solution to the high price of textbooks but in fact precisely this book in electronic format becomes easier to be plowed online by irresponsible elements to be reproduced in order to gain individual benefits only